An electromechanical coupling model of a longitudinal vibration type piezoelectric ultrasonic transducer. (July 2015) - Zhang, Qiang; Shi, Shengjun; Chen, Weishan
Abstract: In this study, an electromechanical coupling model of a longitudinal vibration type piezoelectric ultrasonic transducer is derived. The transducer is a langevin type transducer with an exponential horn which can efficiently focus energy to enlarge vibration amplitude and velocity. Firstly, vibration model of the transducer is built. Vibration shape and resonance frequency of the transducer is obtained. Secondly, based on the vibration model, effective electromechanical coupling model is built. Effective electromechanical coupling coefficient is obtained by combining energy method and equivalent circuit method. Furthermore, the influences of PZT ceramics position on effective electromechanical coupling coefficient and resonance frequency are studied, and the regularity of electromechanical coupling coefficient and resonance frequency versus PZT ceramics position is obtained. Meanwhile, the peak value of effective electromechanical coupling coefficient (34.51%) with its corresponding PZT ceramics position ( L 1 =46 mm) are obtained. Around the peak value, five prototype transducers are fabricated and tested to validate the vibration model and electromechanical coupling model. Vibration shape and resonance frequency are tested with a scanning laser Doppler vibrometer. Electromechanical coupling coefficient is calculated from the testing result of impedance characteristics. At last, comparison between the results of analytical model and experiments are carried out. The comparison indicates that experimental results of resonance frequency and effective electromechanical coupling coefficient are in good agreement with the analytical ones, with the maximum errors 0.673 kHz and 0.83%, separately.